Assessment of DNA damage by extracts and fractions of Strychnos pseudoquina, a Brazilian medicinal plant with antiulcerogenic activity - Santos, F. V. [UNESP]; Colus, I. M S; Silva, M. A. [UNESP]; Vilegas, Wagner [UNESP]; Varanda, Eliana Aparecida [UNESP] (Elsevier, 2006)
Strychnos pseudoquina St. Hil. is a native plant of the Brazilian Savannah, used in popular medicine to treat a number of conditions. Since it contains large quantities of alkaloids with proven antiulcer activity, we tested the genotoxic potential of crude extracts and fractions containing alkaloids and flavonoids from the leaves of this plant, on Salmonella typhimurium and performed the micronucleus test on peripheral blood cells of mice treated in vivo. The results showed that the methanol extract of the leaves of S. pseudoquina is mutagenic to the TA98 (-S9) and TA100 (+S9, -S9) strains of Salmonella. The dichloromethane extract was not mutagenic to any of the tested strains. Fractions enriched with alkaloids or flavonoids were not mutagenic. In vivo tests were done on the crude methanol extract in albino Swiss mice, which were treated, by gavage, with three different doses of the extract. The highest dose tested (1800 mg/kg b.w.) induced micronuclei after acute treatment, confirming the mutagenic potential of the methanol extract of the leaves of S. pseudoquina. In high doses, constituents of S. pseudoquina compounds act on DNA, causing breaks and giving rise to micronuclei in the blood cells of treated animals. © 2006 Elsevier Ltd. All rights reserved.
Keywords: Ames test; Micronucleus; Mutagenicity; Salmonella typhimurium; Strychnos pseudoquina; alkaloid; antiulcer agent; dichloromethane; flavonoid; methanol; plant extract; strychnos pseudoquina extract; unclassified drug; animal cell; animal experiment; blood cell; body weight; controlled study; DNA damage; DNA strand breakage; drug megadose; female; genotoxicity; in vivo study; male; medicinal plant; micronucleus; mouse strain; mutagenicity; nonhuman; plant leaf; Administration, Oral; Animals; Anti-Ulcer Agents; Chemical Fractionation; Dose-Response Relationship, Drug; Female; Male; Methanol; Mice; Micronuclei, Chromosome-Defective; Micronucleus Tests; Mutagens; Plant Extracts; Plants, Medicinal; Reticulocytes; Ribosomal Proteins; Strychnos; Animalia; Salmonella